Pola Pertimbangan Hakim dalam Memutuskan Perkara Perceraian di Pengadilan Agama - Azizah, Rizqiyah Rosyidatul (Kosmik Hukum, 2021)
The aim of this research was to determine the patterns of consideration of judges in deciding divorce cases in Sidoarjo Religious Court. This research used normative method with a case approach which is conducted by examining the ratio decidendi. Data was collected through primary legal sources which include several court judgement and secondary legal sources which were obtained from law books and several law journals that wererelated tothe research. It can be concluded from this research that in deciding the divorce case in the Sidoarjo Religious Court, the Panel of Judges uses a pattern of law through the Constantine stage, namely by finding legal facts in advance based on the information of the Plaintiff / Petitioner and witnesses. Next is the Qualification stage where the Panel of Judges assesses and discovers the law of events that have been conferred, while the final stage is the Constituency, namely the Judge's action to give his constitution to the events that have been conferred and qualified, so that in this stage the Panel of Judges has determined the law in passing a decision. Keywords: Divorce, Judicial Consideration, Court Judgement.